2018
DOI: 10.1093/database/bay054
|View full text |Cite
|
Sign up to set email alerts
|

RBPMetaDB: a comprehensive annotation of mouse RNA-Seq datasets with perturbations of RNA-binding proteins

Abstract: RNA-binding proteins (RBPs) may play a critical role in gene regulation in various diseases or biological processes by controlling post-transcriptional events such as polyadenylation, splicing and mRNA stabilization via binding activities to RNA molecules. Owing to the importance of RBPs in gene regulation, a great number of studies have been conducted, resulting in a large amount of RNA-Seq datasets. However, these datasets usually do not have structured organization of metadata, which limits their potentiall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA‐binding proteins, then acts as an oncogene or a suppressor oncogene . In this study, we found that knockdown of MAPKAPK5‐AS1 in CRC cells could lead to changes in related downstream genes, including p15 , p21 , p27 , p57 , KLF2 , and Trail .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA‐binding proteins, then acts as an oncogene or a suppressor oncogene . In this study, we found that knockdown of MAPKAPK5‐AS1 in CRC cells could lead to changes in related downstream genes, including p15 , p21 , p27 , p57 , KLF2 , and Trail .…”
Section: Discussionmentioning
confidence: 64%
“…26 Therefore, the discovery of new CRC-related lncRNAs is of great significance for further understanding the molecular mechanisms of CRC progression and providing clinical therapeutic targets. In this study, we analyzed 2 sources Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA-binding proteins, [27][28][29][30] then acts as an oncogene or a suppressor oncogene. [31][32][33][34][35] In this study, we found that knockdown of MAPKAPK5-AS1 in CRC cells could lead to changes in related downstream genes, including p15, p21, p27, p57, KLF2, and Trail.…”
Section: Discussionmentioning
confidence: 99%
“…While the present study focused on an application in neuroscience and an application in metabolism, the integrated analysis described here can be generalized to other diseases and BPs. Thus, we expect that similar resources for other regulatory mechanisms and proteins, such as RNA-binding proteins 6 , as well as full-length RNA-Seq and proteogenomics data [39][40][41] , will serve as an important foundation for identifying key factors in human diseases and BPs.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-related BPs can be a fruitful direction for studying CIT mechanisms. Given that only approximately 15% of SFs currently have related RNA-Seq data 6 , more RNA-Seq data will be generated, which will fuel our integrated analysis to predict more key factors of CIT in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation